Immunodeficiency, centromeric heterochromatin instability of chromosomes 1, 9, and 16, and facial anomalies: the ICF syndrome. Issue 3 (March 1988) - Maraschio, P; Zuffardi, O; Dalla Fior, T; Tiepolo, L
Abstract : Instability of the heterochromatic centromeric regions of chromosomes 1, 9, and 16 associated with immunodeficiency was found in a four year old girl. Similar phenotypic and chromosomal abnormalities were described in a previous patient studied by us and in four other published cases. All these patients have facial anomalies in addition to combined immunodeficiency and chromosomal instability. Stretching of the heterochromatic centromeric regions of chromosomes 1, 16, and to a lesser extent, 9 and homologous and non-homologous associations of these regions were the most common cytogenetic findings in all the patients. Multi-branched configurations and whole arm deletions of chromosomes 1 or 16 or both were also found. Comparing clinical and chromosomal data we conclude that immunodeficiency, centromeric heterochromatin instability, and facial anomalies form a new syndrome, for which we propose the acronym ICF. A mutation interfering with the normal process of condensation of part of the centromeric heterochromatin is postulated as the basic chromosome defect in this syndrome.